Pembelajaran Kitab Kuning Siswa Pemula dengan Media Digital di Ma'had Rahmaniyah - Ahmad Mujib; Yoseph Salmon Yusuf; Muhammad Akrom; Tom Amrozi (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2024)
The yellow book is one of the main sources in Islamic religious education and contains various scientific disciplines such as fiqh, hadith, tafsir, and history. However, learning the yellow book often faces challenges, especially for beginner students who still do not have a strong knowledge base in Arabic and the yellow book learning methodology. The use of digital media allows for more active interaction between students and learning materials. The research method used in this research is descriptive-qualitative research. The data collected was analyzed descriptively to reveal the intensity of learning the yellow book. The digital media used include mobile applications, online learning platforms, and other digital resources relevant to yellow book learning. The aim of this research is to make it easier for novice students in Mahad to study the Yellow Book using digital media, where digital can almost certainly not be separated from teenagers. The results of the research show that the use of digital media in learning the yellow book for beginner students at Ma'had Rahmaniyyah Al Islamy Bogor provides several significant benefits. First, digital media helps students gain easier and more flexible access to yellow book material. They can access text, audio, video, and other learning resources online, anytime and anywhere.